Investigating the nasal cycle using unilateral peak nasal inspiratory flow and acoustic rhinometry minimal cross‐sectional area measurements. (26th April 2019) - Tan, Martin Fan Min; Whitcroft, Katherine Lisa; Mehta, Nishchay; Schilder, Anne; Leung, Terence S.; Andrews, Peter J.
Abstract: Objective: To plot the nasal cycle using unilateral peak nasal inspiratory flow (UPNIF) and unilateral minimal cross‐sectional area (UMCA) readings demonstrating a linear relationship in normal nasal function. Additionally, to determine how this changes in abnormal nasal function. Design: A cross‐sectional study measuring UPNIF and UMCA in controls demonstrating normal nasal function and in patients with nasal obstruction. Setting: Royal National Throat Nose and Ear Hospital, London. Participants: A total of 39 participants, 26 controls and 13 patients, were recruited. Controls exhibited normal nasal function with SNOT‐22 <5. Patients nasal obstruction symptoms secondary to inflammation or structural abnormality with SNOT‐22 >9. Main Outcome Measures and Results: Airflow rates and resistance values were derived from UPNIF and UMCA measurements respectively based on Poiseuille's laws. Ratios between right and left UPNIF and UMCA values were taken to adjust for confounding factors. The relationship of 1/ Resistance Ratio and Airflow Rate Ratio demonstrated a linear of direct proportionality of strong correlation and statistical significance (correlation coefficient = 0.76, P « 0.01). This suggests that data points from controls with a normal nasal cycle lie closely along the regressed line, whilst those lying significantly away were shown to belong to patients with nasal dysfunction. Olfactory dysfunction appears to be a sensitive discriminator in predicting this. Conclusion: This study demonstrates the directly proportional relationship of 1/ Resistance Ratio and Airflow Rate Ratio in normal nasal function. Furthermore, nasal pathology can be predicted if data points lie significantly outside these normal limits. Further studies are needed to validate exact normal and abnormal thresholds.